Does social media marketing enhance brand loyalty? identifying mediators relevant to local fast food industries - Yuswita, Effy; Maulidah, Silvana (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2024)
The increasing growth of businesses has intensified competition within various industries, particularly in the local fast food sector. One effective marketing strategy that can be employed is social media marketing. Consequently, it is essential to conduct research to analyze the impact of perceived social media marketing activities on brand loyalty, with brand awareness serving as an intervening variable. The objective of this study was to examine the influence of perceived social media marketing activities on enhancing brand loyalty. This research was conducted among consumers of local fast food in the Malang Raya region, utilizing convenience sampling techniques. The analysis was performed using SEM-PLS 7.0. The findings indicate that social media marketing activities have a positive and significant effect on local brand awareness and local brand loyalty. However, local brand awareness does not significantly mediate local brand loyalty. Electronic word of mouth (E-WOM) effectively mediates the connection between social media marketing and brand loyalty. In contrast, nationality did not effectively moderate the influence of social media marketing, brand awareness, and electronic word of mouth on brand loyalty. Thus, in the current era, massive social media activity within the local fast food industries can positively impact brand loyalty.